Affective politics and non-sovereign identity. Issue 1 (2nd January 2020) - Aryal, Yubraj
ABSTRACT: The paper proposes a new political philosophy of non-sovereign identity based on the model of politics without coercive sovereignty as a source of our political life. It argues that the formation of our identity is not only determined by the existing power relations, but also by our capacity and strategy to work on our own creative self-formation or self-fashioning. The paper combines Michel Foucault's ethical project of self-fashioning and Gilles Deleuze and Félix Guattari's idea of 'lines of flight' together invoking Lauren Berlant's idea of 'the political' in order to observe the constitution of non-sovereign identity beyond and within the given power relations.